Study of modulation doping and ridge height effects in InAs/GaAs quantum dot lasers - Wang, Rui (2012)
Recently, the rapid development of the networks requires fast and stable laser sources. Since quantum dot (QD) lasers are expected to have low threshold current, high characteristic temperature, high material gain, and high differential gain over conventional quantum well (QW) lasers, they have been studied intensively. However, the actual performance of QD lasers has not achieved high speed advantage over QW lasers due to several factors such as the low density of QDs and the closely spaced energy states of the QD holes. Therefore, the use of multiple stacked QD layers and p type modulation doping has been proposed to improve the gain properties and the temperature sensitivities of QD lasers. In this thesis, we study the 1.3µm ten-layer InAs/InGaAs/GaAs quantum dot lasers with different doping concentrations. The main focus of the study is the modal gain characterization. The objective is to investigate the various factors affecting the laser modal gain and, hence, to suggest conditions for the laser growth and fabrication that will improve the QD laser performance. The temperature dependent modal gain of QD lasers with different doping levels was investigated for a better understanding regarding the p type modulation doping effect. The modal gain of the lasers with different ridge heights was also measured to optimize the fabrication process. In addition, experiments conducted in the continuous wave and pulsed modes on the lasers with different doping densities help us to understand the doping effect on the device self-heating.